2010
DOI: 10.1177/0091270010361256
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Modulation of Oxytocin Release

Abstract: Analgesia or anesthesia is frequently used for women in labor. A wide range of opioid analgesics with vastly different pharmacokinetics, potencies, and potential side effects can be considered by physicians and midwives for laboring patients requesting pain relief other than a labor epidural. The past 50 years have seen the use of the classic mu opioid agonist morphine and other opioids diminish markedly for several reasons, including availability of epidural anesthetics, side effects, formulary restrictions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Moreover, although Lithium (You et al, 2001) and Valproate (Štefánik et al, 2015) are reported to increase OXT release in rats and to increase OXT mRNA expression in rat hypothalamic PVN and SON, the IOD of OXTimmunoreactivity of the mood disorder patients who had been administered these compounds (IOD: 24.41,27.39,and 18.06) were fully within the range of the other mood disorder patients (from 16.06 to 40.91, mean value 24.02). Furthermore, a benzodiazepine, such as chlordiazepoxide, was shown to inhibit OXT release in response to noxious stimuli (Yagi and Onaka, 1996), and chronic morphine treatment in rat inhibited OXT synthesis (Morris et al, 2010;You et al, 2001). In our study, more mood disorder patients (n = 9) than control subjects (n = 3) were given diazepines, and more mood disorder patients (n = 9) than control subjects (n = 3) were exposed to morphine.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, although Lithium (You et al, 2001) and Valproate (Štefánik et al, 2015) are reported to increase OXT release in rats and to increase OXT mRNA expression in rat hypothalamic PVN and SON, the IOD of OXTimmunoreactivity of the mood disorder patients who had been administered these compounds (IOD: 24.41,27.39,and 18.06) were fully within the range of the other mood disorder patients (from 16.06 to 40.91, mean value 24.02). Furthermore, a benzodiazepine, such as chlordiazepoxide, was shown to inhibit OXT release in response to noxious stimuli (Yagi and Onaka, 1996), and chronic morphine treatment in rat inhibited OXT synthesis (Morris et al, 2010;You et al, 2001). In our study, more mood disorder patients (n = 9) than control subjects (n = 3) were given diazepines, and more mood disorder patients (n = 9) than control subjects (n = 3) were exposed to morphine.…”
Section: Discussionmentioning
confidence: 53%
“…One of the most common intrapartum procedures associated with synOT is epidural anesthesia. Since opioids have an inhibitory effect on secretion of oxytocin (via mu and kappa receptors) [79] synOT is often required after the administration of an epidural. While the half life of synOT is only 10–12 min or less [80] and intrapartum endogenous oxytocin levels correlate with synOT dosage rate [81], recent evidence suggests the interactions between epidural and synOT may modulate the oxytocin system beyond labor [82].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Evidence of opioid–OXT interactions is indeed well established. Endogenous opioids are involved in the modulation of OXT release into the brain and the periphery via mu- and kappa-receptors expressed on OXT-secreting neurons (2326). Even though the opioidergic modulation of OXT release may account for many shared effects, the interplay of these two systems does not probably end with that.…”
Section: Introductionmentioning
confidence: 99%